PERANCANGAN DISTRIBUTION MIX GUNA MENINGKATKAN PENJUALAN AIDEN - Antonio Tirta Sanjaya (Universitas Ciputra Surabaya, 2016)
AIDEN distributes its products through online store, exhibitions, and consignment. The problem happens when there is no exhibition. In such event, the sales will decrease. On the other hand, sales improve when an exhibition is held. No proper attention has been given to the company’s facilities, inventory, transportation, communication, and unitization. Facts suggest that AIDEN needs an effective and efficient distribution strategy to increase its sales. The purpose of this study is to design a Distribution Mix to increase AIDEN’s sales. Purposive sampling is used to select the study samples, which include competitors and customers. This research is a qualitative research with interview and observation as data collection methods. Study results suggest that the company’s physical distribution can be made effective using exhibitions, online media such as websites, social media such as Instagram, and market places. Conclusively, the outcomes of this research can be used to design a Distribution Mix strategy for AIDEN.